SURVEI TINGKAT KONDISI FISIK ATLET JUDO KOTA MALANG - Akbar Ilham (Sport Pedagogy Journal, 2022)
AbstrakThis study aims to determine the level of physical condition of the athletes of the Malang city judo team in 2022. Instruments in data collection in this study used tests and measurements of physical conditions consisting of strength (Back dynamometer, Leg dynamometer, Push Up) , agility and flexibility (Standing Trunk Flexion) . The subjects of this study were futsal athletes in Malang as many as 7 athletes. which has been data and collected by researchers in the form of documents taken from the FIK UM talent scouting team in collaboration with KONI Malang City, so that the data is data that is already available (exposed facto). Based on the results of the study, it can be seen that the Physical Condition of the Malang City Judo athletes in the very good category is 0.00% (0 athletes), in the good category 11.76% (2 athletes), in the medium category 76.48% (3 athletes), in the less category by 11.76% (2 athletes) and in the less category 0.00% (0 athletes). The conclusion is that the physical condition of the Judo athletes in Malang is in the sufficient category.Kata kunci: physical condition; judo;